A systematic review and meta-analysis to evaluate the clinical outcomes in COVID-19 patients on angiotensin-converting enzyme inhibitors or angiotensin receptor blockers. Issue 2 (15th June 2020) - Grover, Abhinav; Oberoi, Mansi
Abstract: Introduction: Angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) share their target receptor site with the SARS-CoV-2 virus, that may cause ACE2 receptor up-regulation which raised concerns regarding ACEI and ARB use in COVID-19 patients. However, many medical professional societies recommended their continued use given the paucity of clinical evidence, but there is a need for an updated systematic review and meta-analysis of the latest clinical studies. Methods and results: A search was conducted on PubMed, Google Scholar, EMBASE, and various preprint servers for studies comparing clinical outcomes and mortality in COVID-19 patients on ACEIs and/or ARBs, and a meta-analysis was performed. A total of 16 studies were included for the review and meta-analysis. There were conflicting findings reported in the rates of severity and mortality in several studies. In a pooled analysis of four studies, there was a statistically non-significant association of ACEI/ARB use with lower odds of developing severe disease vs. non-users [odds ratio (OR) = 0.81, 95% confidence interval (CI): 0.41–1.58, I 2 =50.52, P -value = 0.53). In a pooled analysis of six studies, there was a statistically non-significant association of ACEI/ARB use with lower odds of mortality as compared with non-users (OR = 0.86, 95% CI = 0.53–1.41, I 2 = 79.12, P -value = 0.55). Conclusion: It is concluded that ACEIs and ARBs should be continued in COVID-19 patients, reinforcing the recommendations made by several medical societies. Additionally, the individual patient factors such as ACE2 polymorphisms which might confer higher risk of adverse outcomes need to be evaluated further.